Defence Industry Applications of Autonomous Agents and Multi-Agent Systems - Pěchouček, Michal (Springer, 2017)
Defense and security related applications are increasingly being tackled by researchers and practioners using technologies developed in the field of Intelligent Agent research. This book is a collection of recent refereed papers drawn from workshops and other colloquia held in various venues around the world in the last two years.